Giant Poisson's Effect for Wrinkle‐Free Stretchable Transparent Electrodes. Issue 35 (3rd July 2019) - Wang, Yan; Liu, Qihan; Zhang, Jianming; Hong, Tianzeng; Sun, Wenting; Tang, Lu; Arnold, Eric; Suo, Zhigang; Hong, Wei; Ren, Zhifeng; Guo, Chuan Fei
Abstract: The next generation of flexible electronics will require highly stretchable and transparent electrodes, many of which consist of a relatively stiff metal network (or carbon materials) and an underlying soft substrate. Typically, such a stiff–soft bilayer suffers from wrinkling or folding when subjected to strains, causing high surface roughness and seriously deteriorated optical transparency. In this work, a network with a giant effective Poisson's ratio on a soft substrate is found to be under biaxial tension upon deformation, and thus does not wrinkle or fold, but maintains smooth surfaces and high transparency. Soft tactile sensors employing such network electrodes exhibit high transparency and low fatigue over many stretching cycles. Such a giant Poisson's ratio has the same effect in other systems. This work offers a new understanding of surface instabilities and a general strategy to prevent them not only in flexible electronics, but also in other materials and mechanical structures that require flat surfaces. Abstract : A stiff–soft bilayer often forms wrinkles under a tiny compressive strain, resulting in a rough surface and high light scattering. However, if the stiff layer has a giant Poisson's ratio, it will be wrinkle‐free upon uniaxial stretching, compression, bending, or releasing from prestretching. This principle is useful for flexible transparent electrodes and other applications wherein wrinkles should be avoided.